(3QSGdI aj JaUjd eG bjd aj CHhj GdQShd Udi Gddg Ydjg hSdes - (3GdJhbGOj GdESJGfHhdj GdYKeGfj GdMfaj, GHf ceGd HGTG, ceGd HGTG RGOg, TeS GdOjf, CMeO Hf SdjeGf Hf ceGd HGTG, (B940 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj cQe BOe Ydjg GdSdGe haVd fSdg HaVd EMSGfg hGdUdGI Ydi ef NUg HWgGQI GdfSH hMaX BHGFg hGYde Cf GdSda GNJdahG aj CHhj GdQShd Ydjg GdSdGe gd eGJG Ydi GdcaQ Ce dG? aPgH Edi GdChd LeY efge UGMH GdJjSjQs
(3BNQgG (B:s
(3hEPG JbQQ gPG aMb GdeSde Cf jeSc dSGfg YeG jMd HTQa fSH fHjfG Ydjg GdSdGe HhLg ef GdhLhg hdG NaGA aj EKHGJ GdTQc aj CHhjg ENdGd XGgQ HTQa fSHg GdWGgQ hHGdLedI gPg GdeSCdI djSJ ef GYJbGOjGJ (B((3cPG(B) (3adG MX ddbdH ajgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 133s
(3eYLe GdeDdajf(B: 3 /148s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs